2011
DOI: 10.1097/shk.0b013e31821366f6
|View full text |Cite
|
Sign up to set email alerts
|

Vital Organ Tissue Oxygenation After Serial Normovolemic Exchange Transfusion with HBOC-201 in Anesthetized Swine

Abstract: This study determined the effects of serial, normovolemic, stepwise exchange transfusions with either 6% human serum albumin (HSA) or the hemoglobin-based oxygen carrier, HBOC-201, on tissue oxygenation of the heart, brain and kidney in intact anaesthetized pigs. Exchange transfusions to 10%, 30% and 50% of the pigs total blood volume were completed at a withdrawal rate of 1.0 ml/kg/min followed by an infusion rate of 0.5 ml/kg/min of HBOC-201 or iso-oncotically matched 6% HSA. Measurements included invasive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Furthermore, no thrombosis or infarction was detected after DCLHb administration. Lesion incidence and severity were reduced by polymerization [81], consistent with reports that such findings have not been observed after the infusion of larger HBOCs [82,83]. In the context of MI, it is interesting to note that the correlation between molecular size and MI incidence in human clinical trials is opposite to that observed with the formation of these microscopic findings.…”
Section: Direct Myocyte Toxicitysupporting
confidence: 87%
“…Furthermore, no thrombosis or infarction was detected after DCLHb administration. Lesion incidence and severity were reduced by polymerization [81], consistent with reports that such findings have not been observed after the infusion of larger HBOCs [82,83]. In the context of MI, it is interesting to note that the correlation between molecular size and MI incidence in human clinical trials is opposite to that observed with the formation of these microscopic findings.…”
Section: Direct Myocyte Toxicitysupporting
confidence: 87%
“…In the systemic circulation, decreases in CO during HBOC‐201 infusion are due to vasoconstriction in skeletal muscle vasculature rather than ischemia‐ or hypoxia‐induced cardiac dysfunction . Normal blood flow and tissue oxygenation are maintained in vital organs, including in particular, the heart, brain, and kidneys . Hence, HBOC‐201 induces a redistribution of systemic blood from skeletal muscles to vital organs.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation could be that these earlier studies did not use an iso-oncotic colloid or because these studies also included the influences of hypovolemia, anemia or tissue trauma. A literature search for research pertaining to HBOC-201 and iso-oncotic HSA revealed only two other studies (Mongan et al, 2009; Muir et al, 2011). Both investigators utilized the same hemodilution model where swine underwent three transfusions to attain volume exchanges of 10%, 30% and 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding viscosity (measured at room temperature) and oxygen affinity was provided by OPK Biotech. Human Serum Albumin (25% HSA, ZLB Behring AG, Berne, Switzerland) was diluted with normal saline to 5.9% to provide an iso-oncotic volume control solution to HBOC-201 (Mongan et al, 2009; Muir et al, 2011). …”
Section: Methodsmentioning
confidence: 99%